(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: This was a descriptive study conducted in Khartoum. The aim was to compare the prothrombin time, activated partial thromboplastin time and fibrinogen level between type II diabetic patients, hypertensive patient, patients had both diseases and control. Materials and Methods: Analytical experimental study was done in Khartoum state, Sudan, during the period of March 2014 to April 2014 to measure coagulation disturbance among essential hypertensive and diabetes mellitus type II patients. The study included 120 consecutive persons were enrolled; 30 had diabetes type II, 30 had diabetes mellitus type II plus hypertension, 30 had hypertension against 30 healthy individual setting as control. Results: The result found that prothrombin time (PT) was significantly increased in diabetic type II and hypertensive patients compared with control (p-value<0.05) and it was normal among patients with diabetes type II with hypertension compared to control (p-value>0.05). While, it was significantly decreased in patients with diabetes type II with hypertension compared to who had only hypertension or only diabetes, activated partial thromboplastin time (APTT) was significantly increased in diabetic type II and among patients with both diseases compared with control (p-value<0.05); it was also, insignificantly different between hypertensive patients and control (p-value >0.05) but it was significantly increased in patients with both diseases compared to who had only hypertension or only diabetes. Fibrinogen level was significantly increased in diabetic type II and patients with both diseases compared to control (p-value <0.05) and statistically insignificant difference between hypertensive patients and control (p-value >0.05) and significantly increase in patients with both diseases compared to who had only hypertension or only diabetes. Conclusion: Our results was concluded a significant correlation between PT and duration of diseased in patients with both diseases (p-value 0.001). In conclusion, fibrinogen was significantly increased in patients with diabetes plus hypertension compared to patients with hypertension or patients with diabetes type II. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.424-429